Business ethics in Islam - Qādrī, Ḥusain Muḥīuddīn (Islamic Business and Finance Ser., 2019)
Islamic Business Finance is based on strong ethical regulations as suggested by Islamic Literature, such as the Quran and the Traditions of the Prophet of Islam, and could be considered as a subclass of the wider subject of ethical standards in business. This book highlights the basic principles of Islamic Business ethics and their implication in today's global business environment. It highlights the most important features of Islamic banking and finance in relation to the core principles of Shariah law. It is the most comprehensive book to date, in terms of the number of Quranic verses and traditions of the Prophet relating to this subject, which are interspersed throughout the text. It explains how ethics are defined both in general terms and within the context of an Islamic perspective. In addition, it provides a logical interpretation of Islamic principles of business ethics, while keeping in view thethrough the use of contemporary business practices. Topics such as digital currencies, money laundering, etc. are discussed at length. This book also discusses the new and emerging ethical issues faced by business and industry globally. This book will be a valuable reference guide for students, teachers and researchers of Islamic banking and finance.